Islamic Law and Terrorism in Indonesia - Ramlani Lina Sinaulan (UIN Sunan Gunung Djati Bandung, 2016)
Jihād and terrorism are not the same. In the context of sharia that implementation of the jihād has parameters measured with a layer of ethics based on the commands Al Quran and the Hadith of Prophet and the explanation the Ulama. Muslims in Indonesia views that the essentially not much different from the views on jihād and terror in other Islamic countries, especially the Middle East. In the context of Islamic law, jihād has multi spectral studies, but none of these studies that equate the meaning of jihād with terrorism, or none of them agreed that acts of terror as has been demonstrated by radical groups that are part of the concept Islam.